Effect of long-term rotation on astigmatism following EVO-toric intraocular collamer lens implantation - Chen, Xun; Miao, Huamao; Cheng, Mingrui; Lin, I-Chun; Li, Boliang; Jiang, Yinjie; Lei, Yadi; Wang, Xiaoying; Zhou, Xingtao (Frontiers in Medicine, 2023)
Objective: To evaluate the effect of long-term rotation on astigmatism following Evolution-toric intraocular Collamer lens (EVO-TICL) implantation.Methods: Forty eyes of 22 patients were enrolled in this prospective study. Visual acuity, refractive parameters, and axial position of the EVO-TICL by OPD-Scan III aberrometer were measured preoperatively, 1 month and 3 years postoperatively.Results: Last visit, the safety index was 1.32±0.15 and the efficacy index was 1.01±0.23. The best-fitting curve of the attempted versus achieved correction was y=0.9751x+0.001. The mean spherical equivalent (SE) decreased from −8.94±2.72D preoperatively to 0.06±0.24D and −0.36±0.46D 1 month and 3 years postoperatively, respectively. The mean target and surgical induced astigmatism were 1.55±0.61D and 1.67±0.94D 3 years postoperatively. The average expected axis of the TICL was -1.15±9.07 (-21-19°). One month and 3 years postoperatively, the average actual axis was -0.70±9.86(-20-20°) and -0.35±11.72(-25-30°), respectively. The absolute rotation of the TICL was 3.70±4.42(0-22°) and 6.00±6.70(0-32°) 1 month and 3 years postoperatively, respectively (P<0.001).The expected astigmatism was -0.10±0.12D, and the mean actual astigmatism was -0.21±0.30D and -0.44±0.45D 1 month and 3 years postoperatively, respectively. The mean absolute rotation without postoperative astigmatism was 3.73±2.69(0-9°) and 1.67±1.66(0-5°) for low (<2D) and high (≥2D) astigmatic TICL, respectively (P<0.05).Conclusion: EVO-TICL implantation is safe and effective, with good predictability and stability. OPD-Scan is a fast device to detect the axial position of the TICL without mydriasis, and the axial position is relatively stable in the long term postoperatively. A slight rotation of low-astigmatic TICL may not cause postoperative astigmatism, whereas rotation of the high-astigmatic TICL may cause it.